Clinical characteristies of atypical hemolytie uremic syndrome associated with H factor antibody in children - Guan, Na (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2014)
OBJECTIVE: To investigate the clinical characteristics, renal pathology, treatment and prognosis of children with atypical hemolytic uremic syndrome associated with H factor antibody